Life Satisfaction of Polish football fans - Maciej Wronkowski; Alicja Kostencka; Jolanta E. Kowalska; Aldona Molesztak (Kazimierz Wielki University, 2018)
Introduction: As the popularity and the importance of positive psychology is growing, the level of life satisfaction of people of different backgrounds has been more and more often put to analysis, including life satisfaction of football fans. The issue of football fans' life satisfaction seems to be interesting not only with regard to all football fans in general, but also to members of different football fan groups in the Polish stadiums. Thus, the present study attempts to determine the level of life satisfaction among Polish football fans and the differences between their groups. Material and methods: The research used the method of a diagnostic online survey and was conducted on a sample of 775 people (148 women and 627 men) who actively participate in sports events as football fans. The respondents in the survey were divided into 4 groups depending on their declared affiliation to the fan group: Supporters (so called "Pikniki" or Picnicking Fans), Ultras, Hooligans and Hardcore Football Fans (Kibole). Results: The life satisfaction level of Polish football supporters is medium or high across all fan groups: Supporters, Ultras, Hardcore Football Fans as well as Hooligans. Therefore, it may be concluded that their life satisfaction is on a similar level. Considering the absence of statistically significant differences between particular groups regarding life satisfaction, it is likely that some determinants of happiness vital for the group of Hooligans as fanatic supporters of football and their 'own' football club may be also characteristic for other groups of supporters.